Acinopus sabulosus and A. lepeletieri from north-west Africa are two distinct species (Coleoptera: Carabidae: Harpalini) - Kataev, Boris M.; Wrase, David W. (Zootaxa, 2015)
Based on examination of the type specimens and additional material from various localities, Acinopus lepeletieri Lucas, 1846 is treated as a distinct species from Algeria and Tunisia, not as a synonym of A. sabulosus (Fabricius, 1792). The distinctive features of these two species and their distribution are described. The absence of any newly collected material of A. lepeletieri argues for the possibly extinction of this species as a result of destruction of its natural biotopes. Lectotype is designated for Scarites sabulosus Fabricius, 1792.